Early history of the Northern Wisconsin Co-Operative Tobacco Pool - Gates, Wayne (My University, 1967)
An Early History of the Northern Wisconsin Co-Operative Tobacco Pool is a seminar paper written as partial fulfillment of the requirement for a masters degree at Wisconsin state University at La Crosse. Farmers in Wisconsin have produced tobacco for over a century. In 1922, to market the tobacco, growers organized the Northern Wisconsin Co-Operative Tobacco Pool. From the beginning the Pool tried to persuade growers of its effectiveness, while the tobacco buyers pointed out the weaknesses of the organization. Litigation between the Pool and the tobacco buyers followed. During the fourteen year history of the Pool the organization fought several contract renewal battles. In 1936 the Directors of the Pool decided to release members from their contracts. As a result of this action the Northern Wisconsin Co-Operative Tobacco Pool ceased to exist as a statewide organization. There has been very little research on this topic. Much of the information has come from local newspapers, tobacco industry publications, and interviews with people involved in the tobacco industry.
Keywords: Cooperative marketing of farm produce -- Wisconsin -- History; Northern Wisconsin Co-operative Tobacco Pool -- History; Tobacco -- Wisconsin -- Cooperative marketing -- History